Berbagai Faktor yang Berpengaruh terhadap Partisipasi Lansia dalam Kegiatan Posyandu Plus di Dusun Soragan Desa Ngestiharjo Kecamatan Kasihan Kabupaten Bantul - Urip Widjajono; Irmanita Wiradona; RR Ratih Hardisari (Sanitasi: Jurnal Kesehatan Lingkungan, 2009)
Bantul Regency local government has adapted health development programs through increasing human resource quality, of which the mission is to promote community participation. One of the participation is Posyandu. Since 2004 in Yogyakarta Province, Posyandu Plus has been developed with additional service of Mitra Keluarga counselling, which has flexibel time service and is adjusted to community needs. In Bantul Regency, Soragan Village which are located in Ngestiharjo, Kasihan, is one of the pilot locations. In its implementation, one of Posyandu Plus’s target is elderly people who aged over 60 years. However, the attendance of them only 50 % from the total population lived in Soragan. The objectives of the study were: to understand the implementation of Posyandu Plus, to understand the participation rate of elderly, and to understand the factors which are influenced the participation. Pathanalysis was conducted using AMOSS 4.00 software. The results showed that the Posyandu Plus and its above additional counselling has been finelyimplemented from, by, for and with the community, and the elderly’s participation rate was quite high. It can be concluded that family condition, andknowledge were not significantly influenced the participation. On the other hand; motivation, role of community figures and services of health officerssignificantly influenced the participation.